2022
DOI: 10.3390/ijms23105472
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Environmental Dose Rates Are Responsible for the Increased Susceptibility to Radiation-Induced DNA Damage in Larval Neuroblasts of Drosophila Grown inside the LNGS Underground Laboratory

Abstract: A large amount of evidence from radiobiology studies carried out in Deep Underground Laboratories support the view that environmental radiation may trigger biological mechanisms that enable both simple and complex organisms to cope with genotoxic stress. In line with this, here we show that the reduced radiation background of the LNGS underground laboratory renders Drosophila neuroblasts more sensitive to ionizing radiation-induced (but not to spontaneous) DNA breaks compared to fruit flies kept at the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The result on cell growth was confirmed by subsequent investigations carried out more recently at the Waste Isolation Pilot Plant (WIPP) [4,5]. Presently, several studies, performed using in vitro cell systems and in vivo organisms, report different biological responses in the biological systems growing in Low-Radiation Environment (LRE) like an impaired stress response [6][7][8], reduced cellular defenses against spontaneous mutations [9], higher sensitivity to a challenging irradiation [10][11][12]. The results of these experiments suggest that the natural radiation background plays a "positive" role for biological systems, acting as a conditioning factor that maintains the efficiency of cellular responses.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The result on cell growth was confirmed by subsequent investigations carried out more recently at the Waste Isolation Pilot Plant (WIPP) [4,5]. Presently, several studies, performed using in vitro cell systems and in vivo organisms, report different biological responses in the biological systems growing in Low-Radiation Environment (LRE) like an impaired stress response [6][7][8], reduced cellular defenses against spontaneous mutations [9], higher sensitivity to a challenging irradiation [10][11][12]. The results of these experiments suggest that the natural radiation background plays a "positive" role for biological systems, acting as a conditioning factor that maintains the efficiency of cellular responses.…”
Section: Introductionmentioning
confidence: 74%
“…A common opinion is that environmental radiation plays a role in these phenomena. Direct evidences of the involvement of the environmental radiation field in such effects were obtained, performing specific experiments [5,12]. In these types of experiments, knowledge of the radiation field in the external reference laboratory and the underground laboratory must be deepened [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, a dose of 90 Gy was sufficient to induce more than 95% sterility in females that had mated with males irradiated with one of the X-ray irradiators. This efficiency of X-rays might be related to their characteristics and the different dose rate of X-ray machines as compared with the Foss Model 812, since DNA damage due to radiation in multicellular organisms is dependent on the environmental dose rate 45 . Concerning the characteristics, gamma- and X-rays are waves in the electromagnetic spectrum, and gamma-rays have the shortest wavelength that are typically, but not always, shorter than those of X-rays (range from 10 pico- to 10 nm).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila melanogaster cultured for five generations showed a stress response and chromosomal damage induced by exposure to LBR. This phenomenon had a cross-generational effect ( 53 ). Van Voorhies et al ( 11 ) found that egg-laying rates and larval growth were increased in Caenorhabditis elegans exposed to LBR for 8 months compared to those observed under normal background radiation levels.…”
Section: Biological Research In the Dugementioning
confidence: 99%